PVP - CMC hydrogel: An excellent bioinspired and biocompatible scaffold for osseointegration - Saha, Nabanita; Shah, Rushita; Gupta, Prerak; Mandal, Biman B; Alexandrova, Radostina; Sikiric, Maja Dutour; Saha, Petr (Materials science & engineering. C, Materials for biological applications, 2019)
Fabrication of porous and biologically inspired biomaterials that mimic the formation of microstructural structures of nacre in the form of calcite (CaCO3) and evaluation of the biocompatibility of such organic-inorganic composite scaffold for bone tissue engineering, are focus of this paper. Nacre's self-assembly characteristics are concerned about the development of calcite filled biomineralized scaffold following the nature based biomineralization process and biomimetic applications. The PVP-CMC hydrogel film, comprised of PVP:0.2, CMC:0.8, PEG:1.0, Agar:2.0, Glycerene:1.0 and water:95.0 w/v%; acts as catalyst and template for the nucleation and growth of the inorganic CaCO3 within the scaffold. The PVP-CMC hydrogel (in the dry state) was immersed in ionic solutions (g/100 ml) of Na2CO3 and CaCl2·H2O in different concentrations sets i.e. Set-1: 10.50/14.70; Set-2: 5.25/7.35; Set-3: 4.20/5.88; Set-4: 2.10/2.94; Set-5: 1.05/1.47, Set-6: 0.55/0.55 for 90 min. As a result, "PVP-CMC-CaCO3" hydrogel scaffold was fabricated having bio-inspired structural and functional properties. Cell proliferation and cell viability were examined until 7 days in the presence of "PVP-CMC-CaCO3" scaffolds using permanent cell lines MG63 (human osteosarcoma), L929 (murine fibroblasts) as well as cultures from mouse bone explants (CC-MBE), confirmed that the said hydrogel scaffolds are biocompatible. But, from mechanical strength as well as biocompatibility point of view, scaffolds prepared in Set-1 to 3 ionic solutions were superior. In conclusion, these three calcite filled hydrogel scaffolds are recommended and can be used for osseointegration.
Keywords: Osseointegration; Tissue Engineering; Spectroscopy, Fourier Transform Infrared; viabilita buněk; Cell Line; difrakce rentgenového záření; Hydrogels; Cell Survival; Mechanical properties; Biocompatibility; Biomaterials; hydrogely; PVP-CMC CaCO(3) composites; tkáňové inženýrství; Cell cultures; Animals; X-Ray Diffraction; biokompatibilní materiály; Microscopy, Electron, Scanning; zvířata; Tissue Scaffolds; Biomineralization; myši; buněčné linie; tkáňové podpůrné struktury; Mice; mikroskopie elektronová rastrovací; Biocompatible Materials; osteointegrace; spektroskopie infračervená s Fourierovou transformací